2013
DOI: 10.2147/cia.s52778
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the ankle-brachial index and the complexity of coronary artery disease in older patients

Abstract: BackgroundIn the elderly, the ankle-brachial index (ABI) has greater than 90% sensitivity and specificity for peripheral artery disease identification. A well-known relation exists between peripheral artery disease and the number of diseased coronary vessels. Yet, other anatomical characteristics have important impacts on the type of treatment and prognosis.PurposeTo determine the relation between ABI and the complexity of coronary artery disease, by different anatomical classifications.MethodsThis study was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
(37 reference statements)
0
11
0
2
Order By: Relevance
“…Ankle-brachial index (measured <0.9) is an effective non-invasive tool to detect peripheral arterial disease. Since coronary artery disease and peripheral arterial disease are manifestation of atherosclerotic process, it is considered that ankle-brachial index may also reflect coronary atherosclerotic burden [7]. Few studies have also shown a link between ankle-brachial index and Syntax score, a lesion based angiographic scoring system introduced as a tool to grade the complexity of coronary lesions [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ankle-brachial index (measured <0.9) is an effective non-invasive tool to detect peripheral arterial disease. Since coronary artery disease and peripheral arterial disease are manifestation of atherosclerotic process, it is considered that ankle-brachial index may also reflect coronary atherosclerotic burden [7]. Few studies have also shown a link between ankle-brachial index and Syntax score, a lesion based angiographic scoring system introduced as a tool to grade the complexity of coronary lesions [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is higher than other studies which have reported it to be 60-80% in patient with symptomatic peripheral arterial disease. 2 This higher prevalence of CAD in patient with Low ABI in our study may be due to inclusion of all patients with ABI less than 0.9 irrespective of presence of absence of symptoms and very selective angiography of patient with Stable ischemic heart disease.…”
Section: Discussionmentioning
confidence: 62%
“…These patients had more extensive and calcified lesions, suggesting a more aggressive form of atherosclerosis. 2 The ankle-brachial index (ABI), which is a non-invasive and inexpensive measurement used to identify PAD has remarkably high sensitivity and specificity (90%, for each), compared against invasive angiography and can be used as indirect measure of CAD severity. 1 Severity of coronary artery diseases varies from minor plaque to diffuse triple vessel disease with different lesion characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,6) The previous studies have shown PAD correlation with the number of coronary artery lesions and the higher complexity of the lesions. (7,8,9) These correlations might contribute to worse cardiovascular outcomes, especially the acute coronary syndrome (ACS) cases. The aim of this study is to evaluate the correlation abnormal ABI with the risk of ACS patients to have multivessel coronary artery lesions.…”
Section: Introductionmentioning
confidence: 99%